Teaching Sociology in Museums - Marković Savić, Olivera S. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
Education system is situated in formal educational and pedagogical institutions. However, considering that schools are not the only places for education, this paper examines the possibilities of teaching sociology in museums as a form of out-of-classroom learning. Teaching sociology in a museum provides opportunities for developing lasting basic knowledge and life-long learning, establishing and developing aesthetic and critical thinking aspects of students’ personalities, and observing personal lives and experiences within a wider social context. The paper shows suggestions for this type of out-of-classroom learning, teacher’s role in planning and visiting museums, teaching methods and units that can be attained in this form of learning, and a museum as an educational instrument.Learning through collaboration with other institutions in the local community shifts the learning context towards more complex cognitive processes. In the process of joint processing of a phenomenon, constructive discussion is encouraged and carried out in an unconventional form of class. At the same time, the cooperation between the local community and the school is being improved because the school upgrades its role of knowledge transfer to the role of a living centre in the community, and the school is actively involved in the needs of the local community. Among the teaching methods applicable to teaching in a museum, we have singled out a dialogical method and an interactive method because of their closeness to the constructivist approach in which the process of acquiring knowledge is conceived as the creation of the individual and the product of constructions. The essence of the teaching process in modern education lies in competencies among which the most important is that a student learns to learn and apply the acquired knowledge in practice.
Keywords: sociology; teaching; museum; student; teacher